Ambition, federalism, and legislative politics in Brazil - Samuels, David, 1967- (Cambridge University Press, 2003)
In the US House of Representatives, members seek to win repeated reelection whereas politicians in Brazil see the national legislature as a stepping-stone to 'higher' office, in state and local government. This book contributes to the literature on the importance of federalism and subnational politics to understanding national-level politics worldwide.